Relationship between red cell distribution width-to-albumin ratio and major adverse cardiovascular events among individuals with acute myocardial infarction - Chen, Cai; Hua, Xiaoguo; Hu, Rui; Wan, Jun; You, Ya; Yang, Min (Frontiers in Cardiovascular Medicine, 2025)
BackgroundRed cell distribution width (RDW) and albumin have been individually linked to adverse cardiovascular outcomes, but the prognostic value of their composite index, the red cell distribution width-to-albumin ratio (RAR), in AMI patients remains under-explored.MethodsA retrospective cohort study was conducted on 917 AMI patients. The main outcome was in-hospital MACEs, including 28-day death, non-fatal stroke, recurrent myocardial infarction, unplanned revascularization, and hospitalization for heart failure or angina. Multi-variable logistic regression analysis was used to calculate their odd ratio (OR) and corresponding confidence interval (95%CI) with adjustments that assessed the relationship RAR index (categorical or continuous variable) of with MACEs among individuals with AMI. Restricted cubic spline (RCS) models were used to assess the dose-response relationship between RAR index and the incidence of MACEs. In addition, receiver operating characteristic curve (ROC) analysis was fitted to assess the accuracy of RAR index in predicting MACEs.ResultsThe cohort had a mean age of 58.7 ± 9.6 years, with 56% males. Higher RAR quartiles were associated with older age, higher MACEs incidence, and lower BMI, cholesterol, eGFR, and blood pressure (all P < 0.05). After full adjustment, each 1-unit increase in RAR was independently associated with elevated MACEs risk (OR = 1.34, 95% CI: 1.03–1.74, P = 0.030), and the highest RAR quartile (Q4) had a 2.30-fold higher risk than the lowest (Q1, P = 0.005). RCS analysis revealed a non-linear relationship with a critical RAR value of 3.48; above this threshold, MACEs risk increased significantly (OR = 2.17, P = 0.031). RAR showed superior predictive performance (AUC = 0.614) compared to RDW (0.564) or albumin (0.605). Subgroup analyses indicated significant associations in male patients (OR = 1.57, P = 0.002) and those with ST-segment elevation myocardial infarction (STEMI, OR = 1.32, P = 0.045).ConclusionThe predictive value of RAR surpasses that of RDW or albumin alone and varies by sex and AMI subtype. RAR holds promise as a simple, cost-effective biomarker for risk stratification in AMI patients, warranting further validation in prospective studies.